Analyzing the Impact of Corporate Hedging on Enterprise Valuation: Evidence from China - Nasriddinov, Bobur; Kurbonov, Sinbad; Mulbah, Kessellie Traore (European Scientific Journal, ESJ, 2024)
In a dynamic global financial landscape marked by unprecedented turbulence, driven notably by the COVID-19 pandemic, corporate hedging practices emerged as a critical tool for managing risks and preserving enterprise value (EV). This research investigated the intricate relationship between corporate hedging and EV, with a specific focus on Chinese-listed firms spanning the period from 2012 to 2022. Employing an extensive sample of 4,574 Chinese-listed firms, the study examines the role of corporate hedging in shaping enterprise value. The findings support the statistically significant impact of corporate hedging on enterprise. The study further tested the moderating role of ownership structure and corporate governance. The findings reveal that ownership structure and corporate governance moderate the relationship between corporate hedging and enterprise value.